Influence of interfacial interaction on the mechanical properties of amorphous PE/MMT nanocomposites - Yulong Wang; Xiaohong Zhang; Lili Li; Junguo Gao (AIP Advances, 2019)
We carried out molecular dynamics simulations to examine the structural, interfacial, and mechanical properties of amorphous polyethylene/montmorillonite (PE/MMT) nanocomposites loaded with 0 wt. %, 3.3 wt. %, 4.0 wt. %, and 5.1 wt. % of modified organic MMT (O-MMT). The MMT nanoparticles were simulated in two stages: first treated with octadecyl trimethyl ammonium chloride and then doped in amorphous PE. The effects of the O-MMT content on the microstructure parameters (interaction energy, free volume, and interfacial thickness) and macroscopic mechanical properties (Young’s modulus, bulk modulus, and shear modulus) were analyzed. A strong correlation between mechanical properties and interfacial thickness was observed by analyzing the obtained data from simulation, and we verified them through experiments.